Silicon-carbon composite material, preparation method thereof, pole piece and battery

By building cluster structures and multi-layer carbon coating on silicon materials, the problem of poor electrochemical performance of silicon-carbon composite materials is solved, and high capacity, long cycles and excellent rate performance are achieved.

CN119674026APending Publication Date: 2025-03-21NINGBO SHANSHAN NEW MATERIAL TECH

Patent Information

Application Number
CN202411898873.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The electrochemical performance of existing silicon-carbon composite materials is poor, especially the rate performance and cycle performance.

Method used

The silicon-carbon composite material adopts a cluster structure, through multi-layer carbon coating and a unique three-dimensional structure, alleviates the volume expansion of the silicon material and improves the lithium ion transmission pathway.

Benefits of technology

The circulation and rate performance of silicon materials are significantly improved, and high capacity, long cycles and excellent negative electrode material performance are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674026A_ABST
    Figure CN119674026A_ABST
Patent Text Reader

Abstract

The invention discloses a silicon-carbon composite material and a preparation method thereof, a pole piece and a battery. The silicon-carbon composite material comprises a cluster structure and a third carbon layer coating the cluster structure, wherein the cluster structure comprises a plurality of silicon-carbon composite particles, pores are distributed among the plurality of silicon-carbon composite particles, each silicon-carbon composite particle has a core-shell structure, each silicon-carbon composite particle comprises an inner core and an outer shell coating the inner core, each outer shell sequentially comprises a first carbon layer and a second carbon layer in the direction far away from the inner core, the first carbon layer comprises a conductive carbon material with a three-dimensional structure, an annular gap exists between the second carbon layer and the first carbon layer, and the inner core comprises porous silicon nanoparticles. The battery prepared from the silicon-carbon composite material has excellent electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a silicon-carbon composite material and a preparation method thereof, a pole piece and a battery. Background Art

[0002] The development of portable electronic products, electric vehicles and large-scale fixed energy storage is inseparable from the contribution of lithium-ion batteries. The development of lithium-ion batteries is inextricably linked to the development of high-performance active materials. The next generation of lithium-ion batteries requires higher energy density and excellent fast charging performance to meet people's long cycle and fast charging needs. The theoretical capacity of the current mainstream negative electrode material graphite is only 372mAh / g, which can no longer meet current needs. The theoretical capacity of silicon is close to 4200mAh / g (about 10 times that of traditional graphite) and its reserves are abundant. Therefore, it is considered to be the most promising alternative material. However, with repeated cycles, the huge volume expansion of silicon materials (>300%) brings many problems, such as pulverization, contact loss between active particles and conductive agents and current collectors, and unstable solid electrolyte interphase (SEI) formation, which ultimately leads to poor first efficiency, rapid capacity decay and extremely poor rate performance, limiting the rapid development of commercial applications of this material.

[0003] At present, the common method for technicians in this field to alleviate the defects of silicon materials is to coat the outside of the silicon material with a carbon layer to form a carbon-coated silicon material. Chinese patent application CN 118712370A introduces a method for preparing a multi-layer carbon-coated silicon-carbon composite material and its application. The silicon-carbon composite material prepared by the method has a silicon content of about 56%, and the first discharge capacity and efficiency are only about 1500mAH / g and more than 80%, and the capacity retention rate after 100 cycles is only more than 80%, indicating that the performance of silicon materials is still not good, and the rate performance and cycle performance of silicon materials with multi-layer carbon coating still need to be further improved. Summary of the invention

[0004] The technical problem to be solved by the present invention is that the electrochemical performance of silicon-carbon composite materials in the prior art is poor, especially the rate performance and cycle performance are poor, and a silicon-carbon composite material and its preparation method, a pole piece and a battery are provided. The silicon-carbon composite material of the present invention has a cluster structure, which can not only alleviate the volume expansion of silicon materials, but also has a unique three-dimensional structure that enables the performance of silicon materials to be exerted to a greater extent, thereby obtaining a negative electrode material with high capacity, long cycle and excellent rate performance.

[0005] The present invention solves the above technical problems through the following solutions.

[0006] The present invention provides a silicon-carbon composite material, characterized in that it comprises a cluster structure and a third carbon layer covering the cluster structure;

[0007] Wherein, the cluster structure includes a plurality of silicon-carbon composite particles, pores are distributed between the plurality of silicon-carbon composite particles, the silicon-carbon composite particles have a core-shell structure, which includes a core and a shell covering the core, the shell includes a first carbon layer and a second carbon layer in a direction away from the core, the first carbon layer includes a conductive carbon material with a three-dimensional structure, an annular gap exists between the second carbon layer and the first carbon layer, and the core includes porous silicon nanoparticles. The porous silicon nanoparticles are preferably doped with heteroatoms. Wherein, the heteroatoms may be one or more of phosphorus, boron, nitrogen and sulfur, such as nitrogen.

[0008] In the present invention, the cluster structure means that there are at least two silicon-carbon composite particles in the structure.

[0009] In the present invention, the D50 of the silicon-carbon composite material may be 350-400 nm, for example, 355, 365, 375, 385 or 395 nm.

[0010] In the present invention, the silicon content of the silicon-carbon composite material may be 50%-55%, for example, 51.2%, 51.6%, 51.7%, 51.3%, 51.8%, 52.1%, 52.2%, 52.5% or 52.3%.

[0011] In the present invention, the carbon content of the silicon-carbon composite material may be 35%-40%, for example, 38.7%, 39.3%, 38.8%, 38.3%, 39.3%, 39.2%, 38.9%, 38.6% or 38.5%.

[0012] In the present invention, the oxygen content of the silicon-carbon composite material may be 7%-8%, for example, 7.52%, 7.47%, 7.54%, 7.91%, 7.48%, 7.67%, 7.63%, 7.49%, 7.41%, 7.14%, 7.27%, 7.31%, 7.59%, 7.51% or 7.32%.

[0013] In the present invention, the boron content of the silicon-carbon composite material may be 0.5%-1%, for example, 0.72%, 0.71%, 0.69%, 0.73%, 0.74% or 0.70%.

[0014] In the present invention, the phosphorus content of the silicon-carbon composite material may be 0.5%-1%, for example, 0.65%, 0.63%, 0.66%, 0.61%, 0.62%, 0.60% or 0.64%.

[0015] In the present invention, the nitrogen content of the silicon-carbon composite material may be 0.3%-1%, for example, 0.49%, 0.51%, 0.52%, 0.53% or 0.55%.

[0016] The content of each element mentioned above represents the percentage of the mass of each element to the mass of the silicon-carbon composite material.

[0017] In the present invention, the conductive carbon material having a three-dimensional structure may be a carbon nanotube.

[0018] The carbon nanotubes may be conventional in the art, preferably single-walled carbon nanotubes or multi-walled carbon nanotubes, more preferably multi-walled carbon nanotubes, and further preferably alkylated double-walled carbon nanotubes or carboxylated double-walled carbon nanotubes. The alkylated double-walled carbon nanotubes are preferably alkylated double-walled carbon nanotubes having a carbon number of 1 to 20. The inner wall diameter of the carbon nanotubes is preferably 1 to 5 nm, for example 2 to 4 nm.

[0019] The inner wall diameter of the carbon nanotube is preferably 1-5 nm, such as 2-4 nm.

[0020] The present invention also provides a method for preparing a silicon-carbon composite material, which comprises the following steps:

[0021] S1. Performing a first carbon coating on porous silicon nanoparticles to obtain a first precursor; wherein the coating material of the first carbon coating includes a conductive carbon material having a three-dimensional structure;

[0022] S2, coating the first precursor with silicon dioxide to form a silicon dioxide layer to obtain a second precursor;

[0023] S3, mixing the aqueous dispersion of the second precursor and the oil phase solution containing an emulsifier, removing the solvent and performing heat treatment to obtain a third precursor;

[0024] S4, performing a second carbon coating on the third precursor and removing the silicon dioxide layer.

[0025] In the present invention, the inner core is configured as porous silicon, and its porous structure can not only buffer the volume expansion of the silicon material, but also increase the lithium ion transmission pathway and improve the electrical conductivity.

[0026] In a preferred embodiment, before step S1, the method may further include: S0, preparing a porous silicon material. Preferably, the porous silicon material is prepared by a sol-gel method and a magnesium thermal reduction method.

[0027] In some preferred embodiments of the present invention, in step S1, the porous silicon may be a porous silicon material co-doped with B and P, and the preparation method thereof comprises the following steps:

[0028] S0-1, stirring a mixture containing a silicon source, a catalyst, a quaternary ammonium salt, a phosphorus source and a boron source, ultrasonically dispersing the mixture and centrifugally collecting the mixture, and calcining the mixture to obtain mesoporous silica;

[0029] S0-2, calcining the mixture of the mesoporous silica, magnesium powder and halogen metal compound to obtain a porous silicon material precursor;

[0030] S0-3. Etching the porous silicon material precursor in an acid aqueous solution to obtain a B and P co-doped porous silicon material.

[0031] In the present invention, the mass ratio of the silicon source, catalyst, quaternary ammonium salt, boron source and phosphorus source in step S0-1 may be (3.5-7.6): (10-15): (1.5-3.0) (0.2-0.5): (0.1-0.2).

[0032] The silicon source described in step S0-1 can be one or more of ethyl orthosilicate, methyl silane orthosilicate and silicate. Among them, the silicate can be one or more of sodium silicate, potassium silicate, magnesium silicate and iron silicate.

[0033] The catalyst in step S0-1 can be concentrated ammonia water, wherein the concentration of the concentrated ammonia water is preferably 28 wt%.

[0034] The phosphorus source in step S0-1 may be one or more of phytic acid, phosphoric acid and diammonium hydrogen phosphate.

[0035] The boron source in step S0-1 may be one or more of boric acid, triethyl borate and tripropyl borate.

[0036] The quaternary ammonium salt in step S0-1 may be one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride, dodecyldimethylbenzylammonium bromide and hexadecyldimethylbenzylammonium bromide.

[0037] The ultrasonic dispersion time in step S0-1 may be 40-60 min, for example, 55 min.

[0038] In a preferred embodiment, the stirring in step S0-1 is performed in an oil bath at 35°C.

[0039] In a specific embodiment, the stirring time in step S0-1 may be 8-12 hours, for example 10 hours.

[0040] The calcination temperature in step S0-1 may be 500-750°C, for example 600°C.

[0041] The heating rate of the calcination in step S0-1 may be 1-10°C / min, for example 3°C / min.

[0042] The calcination time in step S0-1 may be 6-24 hours, for example 15 hours.

[0043] In a preferred embodiment, the calcination in step S0-1 is performed under an inert atmosphere.

[0044] The inert atmosphere in step S0-1 may be one or more of argon, helium and neon.

[0045] In the present invention, the halogen metal compound in step S0-2 may be one or more of sodium chloride, sodium bromide and potassium chloride.

[0046] The mass ratio of the mesoporous silica, magnesium powder and halogen metal compound in step S0-2 may be 1:(0.85-1):(3-7).

[0047] The calcination temperature in step S0-2 may be 500-800°C, for example 650°C.

[0048] The heating rate of the calcination in step S0-2 may be 1-10°C / min, for example 3°C / min.

[0049] The calcination time in step S0-2 may be 8-20 hours, for example 15 hours.

[0050] In a preferred embodiment, the calcination in step S0-2 is performed under an inert atmosphere.

[0051] The inert atmosphere in step S0-2 may be one or more of argon, helium and neon.

[0052] In the present invention, the acid in the aqueous acid solution in step S0-3 may be one or more of hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid and oxalic acid.

[0053] The concentration of the aqueous solution of the acid in step S0-3 may be 2-6 mol / L, for example 2 mol / L.

[0054] The etching time in step S0-3 may be 5-6 hours, for example 5 hours.

[0055] In a specific embodiment, the first carbon coating in step S1 can be carried out by a conventional carbon coating method in the art.

[0056] In the present invention, a first carbon layer is formed after the first carbon coating step.

[0057] In a preferred embodiment, step S1 uses a solvent gel method to perform a first carbon coating on the porous silicon nanoparticles, which includes the following steps:

[0058] S1-1, ultrasonically dispersing the surfactant and carbon nanotubes in water to form spherical micelles;

[0059] S1-2, adding the coating material monomer, nitrogen source and catalyst, stirring to obtain a sol;

[0060] S1-3, adding porous silicon to obtain a core-shell colloid;

[0061] S1-4, heating and polymerization to obtain carbon-encapsulated porous silicon;

[0062] S1-5, carbonization, the gel polymer forms a first carbon layer, and a first precursor is obtained.

[0063] In the present invention, the molar mass ratio of the surfactant to the carbon nanotubes in step S1-1 may be (0.3-0.65) mol: (0.1-0.5) g, for example, 0.4 mol: 0.2 g.

[0064] In step S1-1, the addition of carbon nanotubes can make up for the defects of the spatial dimension of the phenolic resin carbon layer and improve the electrical conductivity and cycle performance of the silicon-carbon composite material.

[0065] The carbon nanotubes in step S1-1 can be conventional in the art, preferably single-walled carbon nanotubes and / or multi-walled carbon nanotubes, more preferably double-walled carbon nanotubes, and further preferably alkylated double-walled carbon nanotubes or carboxylated double-walled carbon nanotubes. The alkylated double-walled carbon nanotubes are preferably alkylated double-walled carbon nanotubes with a carbon number of 1 to 20. The inner wall diameter of the carbon nanotubes is preferably 1 to 5 nm, for example 2 to 4 nm.

[0066] In step S1-1, the surfactant may be one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride, dodecyldimethylbenzylammonium bromide and hexadecyldimethylbenzylammonium bromide.

[0067] The nitrogen source in step S1-2 can be one or more of p-nitroaniline, melamine, triethylamine, pyridine and azobis(ethylbutyronitrile).

[0068] The catalyst in step S1-2 may be a base compound.

[0069] Wherein, the alkaline compound can be one or more of sodium carbonate, sodium hydroxide and sodium citrate.

[0070] In a preferred embodiment, the coating material monomers in step S1-2 are resorcinol and formaldehyde. More preferably, the molar ratio of resorcinol to formaldehyde is preferably (1-3): (1-3).

[0071] Preferably, the molar ratio of the coating material monomer, nitrogen source and catalyst in step S1-2 to the surfactant in step S1-1 is (1.0-2.0): (0.01-0.09): (0.007-0.03): (0.3-0.65).

[0072] Preferably, the molar ratio of the porous silicon in step S1-3 to the catalyst in step S1-2 is (4.0-6.0): (0.007-0.03).

[0073] Preferably, the polymerization temperature in step S1-4 is 80-100°C.

[0074] Preferably, the polymerization time in step S1-4 is 8-24 hours.

[0075] Preferably, the carbonization temperature in step S1-5 is 550-850°C.

[0076] Preferably, the carbonization time in step S1-5 is 8-24 hours.

[0077] Preferably, the carbonization in step S1-5 further includes rinsing and drying, wherein preferably, the rinsing may be performed with water and / or ethanol.

[0078] In a specific embodiment, the silica coating in step S2 can be carried out using a conventional silica coating method in the art.

[0079] In a preferred embodiment, step S2 comprises the following steps:

[0080] S2-1, mixing a first precursor, a silicon source and an ammonia solution, acid washing, and heat treating to obtain a second precursor;

[0081] S2-2, mixing the aqueous dispersion of the second precursor and the oil phase solution containing an emulsifier, removing the solvent and performing heat treatment to obtain a third precursor.

[0082] The silicon source in step S2-1 can be conventional in the art, preferably a silicate or a silicate. The silicate is preferably ethyl orthosilicate and / or methyl orthosilicate. The silicate is preferably one or more of sodium silicate, potassium silicate, magnesium silicate and iron silicate.

[0083] The mass percentage of ammonia in the ammonia solution in step S2-1 is preferably 25%-30%, for example 28%.

[0084] In step S2-1, the mass volume ratio of the first precursor, the silicon source and the ammonia solution is preferably (1-3) g: (3-10) mL: (240-260) mL.

[0085] The mixing time in step S2-1 is preferably 40-60 min.

[0086] The acid used in the pickling in step S2-1 can be a conventional inorganic acid in the art, such as hydrochloric acid. The pickling generally uses an aqueous solution of an acid, such as an aqueous solution of an acid with a molar concentration of 2M.

[0087] After the acid washing in step S2-1 and before the heat treatment, it is preferred that conventional steps of filtration, washing and drying are also included in the art.

[0088] The temperature of the heat treatment in step S2-1 is preferably 550-900° C. The time of the heat treatment is preferably 8-15 hours. The rate of heating from room temperature to the heat treatment temperature is preferably 1-10° C. / min.

[0089] In a specific embodiment, after step S3, a second precursor having a clustered structure distribution is obtained, which is recorded as a third precursor.

[0090] In step S3, the aqueous dispersion of the second precursor preferably includes a second precursor, a surfactant and water.

[0091] Among them, the surfactant is preferably one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride, dodecyldimethylbenzylammonium bromide and hexadecyldimethylbenzylammonium bromide, such as hexadecyltrimethylammonium bromide.

[0092] In step S3, the ratio of the second precursor, the surfactant and the water is preferably (1-3) g: (0.2-0.65) mol: 300 mL, for example 2.5 g: 0.45 mol: 300 mL.

[0093] In S2-2 of the present invention, the emulsifier may be an emulsifier having a hydrophile-lipophile balance (HLB) of 3-8, preferably an emulsifier having a hydrophile-lipophile balance (HLB) of 4-7, and more preferably one or more of propylene glycol fatty acid esters, diethylene glycol monooleate, glyceryl monostearate and diethylene glycol monolaurate, such as diethylene glycol monooleate or glyceryl monostearate.

[0094] In S3 of the present invention, the oil phase solvent in the oil phase solution containing the emulsifier can be conventional in the art, and is preferably an olefin having 12 to 28 carbon atoms, such as 1-octadecene.

[0095] In S3 of the present invention, the mass percentage of the emulsifier in the oil phase solution containing the emulsifier may be 0.5-1wt%, for example 0.8wt%.

[0096] In S3 of the present invention, the method for removing the solvent may be conventional in the art, such as evaporation. The temperature during the evaporation may be 95-98°C.

[0097] In S3 of the present invention, the temperature of the heat treatment is preferably 450-600° C., for example 550° C. The time of the first heat treatment is preferably 0.5-1.5 h, for example 1 h. The heat treatment is preferably carried out under an inert atmosphere. The inert atmosphere is preferably nitrogen, helium, neon or argon, for example nitrogen.

[0098] In S3 of the present invention, the heat treatment preferably further includes a condensation step.

[0099] In a specific embodiment, the second carbon coating in step S4 can adopt a conventional carbon coating method in the art. In the present invention, after the second carbon coating in step S4, silicon-carbon composite particles with clustered structure distribution and a third carbon layer coated on the surface of the silicon-carbon composite particles are obtained.

[0100] In the present invention, the carbon source in the coating material during the second carbon coating in S4 can be conventional in the art, and preferably includes phenolic resin and / or asphalt, such as phenolic resin.

[0101] Wherein, the carbon source in the coating material includes phenolic resin, and the preparation method of subjecting the third precursor to the second carbon coating preferably includes the following steps: mixing resorcinol, formaldehyde, a catalyst and the third precursor, and performing polymerization reaction and carbonization treatment.

[0102] The molar ratio of the formaldehyde to the resorcinol may be (500-1000): (0.5-1.0), for example 1000: 1. The catalyst may be a base, preferably sodium carbonate, sodium hydroxide or sodium citrate, such as sodium carbonate. The molar ratio of the resorcinol to the catalyst may be (0.5-1.0): (0.007-0.03), for example 0.5: 0.01.

[0103] The polymerization temperature may be 80-100° C., such as 90 or 95° C. The polymerization time may be 8-24 hours, such as 10 hours. After the polymerization and before the carbonization treatment, a drying step is preferably further included.

[0104] In S4 of the present invention, the coating material used for the carbon coating is preferably further added with carbon nanotubes and / or heteroatoms.

[0105] The surfactant is preferably one or more of cetyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride, dodecyldimethylbenzylammonium bromide and cetyldimethylbenzylammonium bromide, for example cetyltrimethylammonium bromide.

[0106] The carbon nanotubes may be conventional in the art, preferably single-walled carbon nanotubes or multi-walled carbon nanotubes, more preferably double-walled carbon nanotubes, and further preferably alkylated double-walled carbon nanotubes or carboxylated double-walled carbon nanotubes. The alkylated double-walled carbon nanotubes are preferably alkylated double-walled carbon nanotubes having a carbon number of 1 to 20. The inner wall diameter of the carbon nanotubes is preferably 1 to 5 nm, for example 2 to 4 nm.

[0107] In step S3, the ratio of the surfactant to the carbon nanotubes in the aqueous dispersion of the second precursor is preferably (0.2-0.65) mmol: (0.1-0.5) g, for example, 0.3 mmol: 0.23 g or 0.5 mmol: 0.23 g.

[0108] The molar ratio of the surfactant to the water is preferably (0.2-0.65):(5000-15000), for example 0.3:8000 or 0.5:8000.

[0109] The ultrasonic dispersion time is preferably 40-60 min, such as 50 min.

[0110] Wherein, when heteroatoms are also added to the coating material, the preparation method of carbon coating the third precursor preferably includes the following steps: mixing the heteroatom source, resorcinol, formaldehyde, a catalyst and the third precursor, polymerization reaction and coating treatment.

[0111] The heteroatom may be one or more of phosphorus, boron, nitrogen and sulfur, such as nitrogen. When the heteroatom is nitrogen, the nitrogen source may be a nitrogen-containing substance, preferably one or more of p-nitroaniline, nitroaniline, melamine, triethylamine, pyridine and azobis(ethylbutyronitrile), such as p-nitroaniline.

[0112] The molar ratio of the heteroatom source to the resorcinol is preferably (0.01-0.09):(0.5-10), for example 0.03:0.5.

[0113] Among them, when carbon nanotubes and heteroatoms are also added to the coating material, the preparation method of carbon coating the third precursor preferably includes the following steps: mixing the surfactant, carbon nanotubes and water, ultrasonic dispersion, mixing with the heteroatom source, resorcinol, formaldehyde, catalyst and the third precursor, polymerization reaction and carbonization treatment.

[0114] In S4 of the present invention, the carbonization temperature may be 600-850°C, such as 650 or 700°C.

[0115] In S4 of the present invention, the carbonization time may be 8-24 hours, for example 15 hours.

[0116] In S4 of the present invention, the method for removing silicon dioxide may be etching. The etching solution used for the etching is preferably a hydrofluoric acid solution. The mass percentage of hydrofluoric acid in the hydrofluoric acid solution is preferably 4-6wt%, such as 5wt%.

[0117] In a preferred embodiment, the product obtained in step S4 is recorded as the fourth precursor, and step S4 is followed by step S5, coating the fourth precursor with a chestnut-shaped carbon layer. Preferably, in step S5, coating the fourth precursor with a chestnut-shaped carbon layer by a chemical bath deposition method comprises the following steps:

[0118] S5-1, ultrasonically dispersing the fourth precursor in a quaternary ammonium salt aqueous solution to obtain a fourth precursor dispersion; adding an aqueous solution containing a nickel salt and an initiator to the fourth precursor dispersion, stirring, adding ammonia water, reacting under stirring, centrifuging, and drying to obtain a composite material A;

[0119] S5-2, heat-treating the composite material A to obtain a composite material B;

[0120] S5-3, adding the composite material B into a surfactant aqueous solution, and sequentially adding a coating material monomer and an initiator, reacting under stirring, centrifuging, washing, and drying to obtain a composite material C;

[0121] S5-4, calcining the composite material C, cooling, and obtaining a composite material D; the composite material D comprises a nickel layer and a carbon layer;

[0122] S5-5. Treat the composite material D with acid to remove the nickel layer, wash, and dry to form a chestnut-shaped carbon layer.

[0123] In the present invention, the quaternary ammonium salt in step S5-1 may be one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride, dodecyldimethylbenzylammonium bromide and hexadecyldimethylbenzylammonium bromide.

[0124] The mass ratio of the fourth precursor to the quaternary ammonium salt in step S5-1 may be (0.5-1.0):(0.009-0.05), for example, 0.8:0.01.

[0125] The nickel salt in step S5-1 may be nickel acetate, nickel nitrate or nickel sulfate, for example, nickel acetate.

[0126] The initiator in step S5-1 may be one or more of potassium persulfate, sodium persulfate and potassium hydrogen persulfate, for example, potassium persulfate.

[0127] The mass ratio of the nickel salt, the initiator and the fourth precursor in step S5-1 may be (0.1-0.5):(0.02-0.1):(0.5-1.0), for example, 0.1:0.05:0.8.

[0128] In a preferred embodiment, the stirring in step S5-1 is performed in an oil bath at 25°C.

[0129] The stirring time in step S5-1 may be 10-60 min, for example 50 min.

[0130] The stirring time in step S5-1 may be 10-30 min, for example 20 min.

[0131] The centrifugal speed in step S5-1 may be 200-300 r / min, for example 250 r / min.

[0132] The temperature of the heat treatment in step S5-2 may be 350-600°C, for example 450°C.

[0133] The constant temperature time of the heat treatment in step S5-2 may be 8-24 hours, for example, 10 hours.

[0134] The heating rate of the heat treatment in step S5-2 may be 1-10°C / min, for example 3°C / min.

[0135] The heating rate refers to the heating rate during the process of heating to the heat treatment temperature.

[0136] In the present invention, the surfactant in step S5-3 may be an anionic surfactant.

[0137] The anionic surfactant may be one or more of sodium dodecylbenzenesulfonate, hexadecyltrimethylammonium p-toluenesulfonate, sodium dodecylsulfonate and sodium α-olefinsulfonate.

[0138] The initiator in step S5-3 may be one or more of potassium persulfate, sodium persulfate and potassium hydrogen persulfate.

[0139] The mass volume ratio of the surfactant, the coating material monomer and the initiator in step S5-3 can be (3-10) mg: (0.1-0.3) ml: (0.25-0.65) g, for example 7 mg: 0.2 ml: 0.38 g.

[0140] In step S5-3, the coating material monomer may be pyrrole and / or pyridine.

[0141] The calcination temperature in step S5-4 may be 650-850°C, for example 650°C.

[0142] The calcination time in step S5-4 may be 8-24 hours, for example 15 hours.

[0143] In a preferred embodiment, the calcination in step S5-4 is performed in an inert atmosphere, which may be high-purity nitrogen, helium, neon or argon.

[0144] The cooling rate of the cooling in step S5-4 may be 10-20°C / min, for example 15°C / min.

[0145] The acid used in the acid treatment in step S5-5 may be one or more of hydrochloric acid, sulfuric acid and nitric acid.

[0146] The concentration of the acid in step S5-5 may be 1-10 mol / L, for example 5 mol / L.

[0147] In the present invention, preferably, the product obtained in step S5 is recorded as the fifth precursor, and after step S5, the method further includes: S6, coating the fifth precursor with a graphene layer.

[0148] The coated graphene layer may be coated using a coating method conventionally used in the art. In a preferred embodiment, step S6 comprises the following steps:

[0149] S6-1, adding the fifth precursor and humic acid into water to obtain a premix, and adding an ammonia solution under stirring;

[0150] S6-2, heating, sintering treatment, cooling;

[0151] S6-3, carbonization, graphene layer is formed in situ after thermal decomposition of humic acid.

[0152] In the present invention, preferably, in step S6-1, the humic acid is humic acid powder.

[0153] Preferably, in step S6-1, the mass ratio of the fifth precursor to the humic acid is (6-15):1.

[0154] In step S6-1, the solid-liquid ratio of the premix may be 1:(10-15), for example, 1:10.

[0155] In step S6-1, the mass concentration of the aqueous ammonia solution may be 22-32%, for example, 28%.

[0156] Preferably, in step S6-1, the amount of the aqueous ammonia solution used allows the humic acid to be completely dissolved.

[0157] In a preferred embodiment, in step S6-1, the ammonia solution is added dropwise, and preferably, the rate of the addition is 100-180 mL / min.

[0158] In step S6-2, the heating temperature may be 80-100°C, for example, 90°C.

[0159] In step S6-2, the sintering temperature may be 200-300°C, for example, 280°C.

[0160] In step S6-2, the sintering time may be 1-3 h, for example, 2 h.

[0161] Preferably, in step S6-2, the sintering is performed in a microwave oven.

[0162] In step S6-3, the carbonization temperature may be 500-850° C., for example, 800° C. The heating rate to the carbonization temperature may be 1-10° C. / min, for example, 3° C. / min.

[0163] In step S6-3, the carbonization time may be 8-15 h, for example, 10 h.

[0164] In a specific embodiment, in step S6-3, the carbonization is performed in a tubular furnace.

[0165] In a preferred embodiment, in step S6-3, the carbonization is performed in an inert atmosphere. Preferably, the inert atmosphere can be selected from one or more of nitrogen, helium, neon and argon. More preferably, the nitrogen is high-purity nitrogen.

[0166] In the present invention, the drying method involved in each step is independently any one of the following ①-③:

[0167] ① Freeze drying, preferably, the drying temperature is -30-(-80)°C; preferably, the drying time is 3-7h;

[0168] ②CO2 supercritical drying, preferably, the drying temperature is 10-40°C; preferably, the drying pressure is 10-15kPa; preferably, the drying time is 1-3h;

[0169] ③ Vacuum drying, preferably, the drying temperature is 80-100°C; preferably, the drying time is 8-24h.

[0170] The present invention provides a silicon-carbon composite material, which is prepared by the preparation method of the silicon-carbon composite material as described above.

[0171] The present invention also provides a pole piece, which comprises the silicon-carbon composite material as described above.

[0172] The present invention also provides a battery, which comprises the pole piece as described above.

[0173] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0174] The reagents and raw materials used in the present invention are commercially available.

[0175] The positive and progressive effects of the present invention are:

[0176] (1) The present invention combines the advantages of silicon material modification, multi-layer carbon coating, and unique cluster structure from the preparation of porous silicon to the construction of cluster structure, so that the volume expansion defect is significantly improved, and the actual capacity of silicon material is improved, thereby showing excellent cycle performance. Among them, there are many gaps between the cluster structures, which buffer its volume expansion. The carbon-coated hollow silicon composite material multiple guarantees the volume expansion and electronic conductivity of the silicon-carbon material, so that the cycle performance is significantly improved.

[0177] (2) In the preferred embodiment, a chestnut-shaped carbon layer is constructed outside the cluster structure to form a homogeneous interconnected structure inside and outside, which can promote and accelerate the transmission of lithium ions and further enhance the suppression of volume expansion, so that it can obtain excellent rate performance and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0178] Figure 1 Schematic diagram of the structure of a single silicon-carbon composite particle in the silicon-carbon composite material obtained in Example 1. 1 is a silicon-carbon composite particle, 11 is a porous silicon nanoparticle, 12 is a first carbon layer, 13 is an annular space, and 14 is a second carbon layer.

[0179] Figure 2 Schematic diagram of the structure of the silicon-carbon composite material obtained in Example 17. 1 is a silicon-carbon composite particle, and 2 is the third carbon layer.

[0180] Figure 3 Schematic diagram of the structure of the silicon-carbon composite material obtained in Example 1. Among them, 1 is a silicon-carbon composite particle, 2 is the third carbon layer, and 3 is a chestnut-shaped carbon layer. DETAILED DESCRIPTION

[0181] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0182] Example 1

[0183] S0: Preparation of porous silicon materials

[0184] Hexadecyltrimethylammonium bromide, boric acid and phytic acid were dissolved in a mixed solution of water and ethanol in a mass ratio of 1.8:0.3:0.12, stirred for 50 min, and then ultrasonically treated for 55 min. Then, 12 mL of concentrated ammonia (28 wt %) was added as a catalyst to catalyze the hydrolysis of the silicon source. Then 6.5 mL of tetraethyl orthosilicate was added to the mixed solution, and the mixed solution was stirred in an oil bath at 35 ° C for 10 h. Finally, the product was collected by centrifugation and washed alternately with water and ethanol for 5 times. The final product was calcined in a tube furnace at 600 ° C for 12 h under nitrogen at a rate of 3 ° C / min to prepare mesoporous silica. Mesoporous silica was mixed with magnesium powder and sodium chloride in a mass ratio of 1: 0.85: 5. Magnesium thermal reduction was carried out in an inert atmosphere with a heating rate of 3 ° C / min and calcined at 650 ° C for 15 h. The calcined mixture was then treated in 2 mol / L hydrochloric acid for 5 h, filtered and dried to obtain a porous silicon material.

[0185] S1: First Carbon Coating

[0186] Hexadecyltrimethylammonium bromide (0.4 mmol) and 0.2g of multi-walled carbon nanotubes (with an inner wall diameter of 3.5nm) were ultrasonically dispersed to be uniformly distributed in deionized water (8mol) to form spherical micelles, on which the multi-walled carbon nanotubes were fixed. Secondly, a mixture of 0.04mmol of triethylamine, resorcinol (0.5 mmol), formaldehyde (0.5 mol) and 0.01 mmol of sodium carbonate was added and stirred for 55min to obtain a surface-stabilized sol. Subsequently, 4.5g of porous silicon material was added and uniformly dispersed to obtain a surfactant-stabilized core-shell colloid. The core-shell colloid was then polymerized at 90°C for 10h to obtain a sol polymer of interlayer carbon encapsulated porous silicon. After drying, it was heated to 650°C at a heating rate of 5°C / min under nitrogen and heat treated for 15h to carbonize the gel polymer, and then repeatedly rinsed with water and ethanol, respectively, and vacuum dried at 90°C for 10h to obtain the first precursor.

[0187] S2: Obtaining the second precursor

[0188] 6.5 mL of tetraethyl orthosilicate and 2.5 g of the first precursor were added to an ammonia solution in sequence, mixed and stirred for 50 min, filtered and cleaned, and pickled with 2 mol / L hydrochloric acid, filtered and cleaned again, and dried; then, the silicon dioxide layer was fixed by heat treatment at 700 ° C at a heating rate of 3 ° C / min for 10 h to obtain a second precursor.

[0189] S3: Obtaining the third precursor

[0190] The uniform dispersion of the second precursor was added to 250 mL of deionized water containing 0.35 mmol of hexadecyltrimethylammonium bromide to form a water-dispersed colloid, which was then mixed with 0.8 wt% of 1-octadecene of diethylene glycol monooleate to form an oil-in-water emulsion. After evaporation at 97 ° C, the assembled second precursor was collected by centrifugation and then heat-treated in air at 550 ° C for 1 h to remove organic matter, and then condensed to form a third precursor distributed in a clustered structure.

[0191] S4: Obtaining the fourth precursor Hexadecyltrimethylammonium bromide (0.45mmol) and 0.2g multi-walled carbon nanotubes were mixed and ultrasonically dispersed for 50min to make them uniformly distributed in deionized water (10 mol) and form spherical micelles for fixation. Secondly, a mixture of 0.03mmol triethylamine, resorcinol (0.5 mmol), formaldehyde (0.5mol) and sodium carbonate (0.01 mmol) was added and stirred continuously to obtain a surface-stabilized sol. Subsequently, 4.5g of the third precursor was added to obtain a surfactant-stabilized core-shell colloid. The core-shell colloid was then polymerized at 90°C for 10h to obtain a carbon-coated third precursor. After drying, it was heat treated at 700°C for 15h under an inert atmosphere (same as below) to carbonize the gel polymer. Finally, the silicon dioxide layer was removed with a 5 wt% HF solution to form a void space to accommodate the large volume change of the silicon material during the charge and discharge process. The resulting product was recorded as the fourth precursor.

[0192] S5: Chestnut-shaped carbon layer

[0193] S5-1. Add 0.8g of the fourth precursor to 50 mL of deionized water dissolved with 0.01g of hexadecyltrimethylammonium bromide, stir, and ultrasonically treat for 20-50min to make the fourth precursor well distributed and preserved. Dissolve 0.1g of nickel acetate and 0.05g of potassium persulfate in another 50 mL of distilled water. After complete dissolution, slowly add to the fourth precursor dispersion. After stirring for 50min, add 17mL of 1.5% ammonia water. Stir again at 25°C in an oil bath. Finally, collect the product by centrifugation and vacuum dry at 90°C for 10h to obtain composite material A.

[0194] S5-2. The nanoparticles of composite material A were then heated at 450°C at a rate of 3°C / min in high-purity nitrogen and kept at this temperature for 10 h to prepare a core-shell chestnut-shaped structure composite material B.

[0195] S5-3, dissolve 7 mg of sodium dodecylbenzene sulfonate in 250 mL of deionized water. Add 0.1 g of composite material B and stir for 25-55 min; put 0.2 mL of pyrrole into an ice bath at 0-5°C and stir for 50 min. At the same time, dissolve 0.38 g of potassium persulfate in 40 mL of distilled water. After complete dissolution, add it to the pyrrole mixed solution and stir for 24 h at a reaction temperature below 5°C. At the end of the reaction, collect the product by centrifugation, wash with distilled water and ethanol in turn to remove impurities, and vacuum dry at 90°C for 15 h to obtain composite material C.

[0196] S5-4. Finally, the composite material C was calcined at 650°C (cooling rate of 15°C / min) for 15 h in an argon atmosphere to obtain a composite material D coated with a nitrogen-doped carbon layer.

[0197] S5-5, remove the nickel oxide layer in the composite material D with 5 mol / l acid, and wash the material with deionized water to neutrality. Finally, vacuum dry at 90°C for 20 hours to obtain the final product. The structural schematic diagram of a single silicon-carbon composite particle in the obtained silicon-carbon composite material is shown in Figure 1 As shown, the structural schematic diagram of the obtained silicon-carbon composite material is as follows Figure 3 shown.

[0198] Example 2

[0199] The difference from Example 1 is that in step S0, 5.5 mL of methyl orthosilicate is added instead of ethyl orthosilicate, and the remaining steps are the same as in Example 1.

[0200] Example 3

[0201] The difference from Example 1 is that in step S0, the mass ratio of mesoporous silica to magnesium powder and sodium chloride is 1:0.85:4.5, and the remaining steps are the same as Example 1.

[0202] Example 4

[0203] The difference from Example 1 is that melamine is used instead of triethylamine in step S1, and the remaining steps are the same as Example 1.

[0204] Example 5

[0205] The difference from Example 1 is that in step S2, methyl orthosilicate of silane is used instead of ethyl orthosilicate, and the remaining steps are the same as Example 1.

[0206] Example 6

[0207] The difference from Example 1 is that the amount of ethyl orthosilicate added in step S2 is 7.5 mL, and the remaining steps are the same as Example 1.

[0208] Example 7

[0209] The difference from Example 1 is that the concentration of diethylene glycol monooleate in step S3 is 0.6wt%, and the remaining steps are the same as Example 1.

[0210] Example 8

[0211] The difference from Example 1 is that in step S3, glyceryl monostearate is used instead of diethylene glycol monooleate, and the remaining steps are the same as Example 1.

[0212] Example 9

[0213] The difference from Example 1 is that the surfactant in step S4 is 0.55 mmol, and the remaining steps are the same as Example 1.

[0214] Example 10

[0215] The difference from Example 1 is that the amount of resorcinol added in step S4 is 0.8 mmol, and the remaining steps are the same as Example 1.

[0216] Embodiment 11

[0217] The difference from Example 1 is that the amount of the third precursor added in step S4 is 5 g, and the remaining steps are the same as Example 1.

[0218] Example 12

[0219] The difference from Example 1 is that the polymerization temperature in step S4 is 95° C., and the remaining steps are the same as Example 1.

[0220] Embodiment 13

[0221] The difference from Example 1 is that the heat treatment temperature in step S4 is 650° C., and the remaining steps are the same as Example 1.

[0222] Embodiment 14

[0223] The difference from Example 1 is that the amount of the fourth precursor added in step S5-1 is 0.6 g, and the remaining steps are the same as Example 1.

[0224] Embodiment 15

[0225] The difference from Example 1 is that the amount of pyrrole added in step S5-3 is 0.1 mL, and the remaining steps are the same as Example 1.

[0226] Example 16

[0227] The difference from Example 1 is that the calcination temperature in step S5-4 is 700°C, and the remaining steps are the same as Example 1.

[0228] Embodiment 17

[0229] The difference from Example 1 is that there is no step S5 (ie, no chestnut-shaped structure is constructed), and the remaining steps are the same as those in Example 1. The structural schematic diagram of the obtained silicon-carbon composite material is shown in FIG. Figure 2 shown.

[0230] Comparative Example 1:

[0231] The difference from Example 1 is that the negative electrode material is pure silicon powder.

[0232] Comparative Example 2:

[0233] The difference from Example 1 is that there is no step S2 (ie, the hollow carbon layer is not constructed), and the remaining steps are the same as those in Example 1.

[0234] Comparative Example 3:

[0235] The difference from Example 1 is that step S3 is not performed (ie, no cluster structure is formed), and the remaining steps are the same as Example 1.

[0236] Effect Example 1

[0237] Physical and chemical properties test:

[0238] The inductively coupled plasma (ICP) method was used to test the element content (silicon, carbon, oxygen, boron, phosphorus, and nitrogen content) in the silicon-carbon composite material prepared by the present invention. The test method is as follows: (1) Pre-treatment by microwave digestion method, 0.5 g of the silicon-carbon composite material prepared by the embodiment and the comparative example was placed in a digestion tank, 3 mL of concentrated nitric acid and 9 mL of concentrated sulfuric acid were added in sequence with a liquid adder, and the mixture was shaken well; and the mixture was kept at a constant temperature of 160°C for 3 min, 180°C for 3 min, 200°C for 10 min, and 220°C for 10 min, and then cooled to room temperature, filtered with quantitative filter paper, and the filtrate was placed in a 50 mL volumetric flask as the test solution; (2) The above test solution was tested in the PerkinElmer ICP spectrometer Avio™ 200 device; the test condition was an air pressure of 2 MPa.

[0239] The D50 of the silicon-carbon composite materials prepared in the examples and comparative examples was tested using a Malvern particle size tester.

[0240] Conductivity model Measured at room temperature.

[0241] The charge transfer resistance was measured by electrochemical impedance spectroscopy (compacted density 1.65 g / cm 3 )get.

[0242] The above physical and chemical results are shown in Table 1 below.

[0243] Table 1

[0244]

[0245] Effect Example 2

[0246] Lithium-ion button cell battery testing:

[0247] The preparation method of the button cell used for testing the electrochemical performance is as follows: the silicon-carbon composite material prepared in the embodiment and the comparative example is mixed evenly with the conductive agent (KS-6), CMC, and SBR in a mass ratio of 95.5:1.5:1.5:1.5, and applied on a copper foil with a compaction density of 1.60 g / cm 3 , vacuum dried as the negative electrode, lithium metal as the counter electrode, the electrolyte using 1MLiPF6 ethylene carbonate (EC) and dimethyl carbonate (DMC) in a mass ratio of 1:1, the separator is PE / PP / PE composite film, and assembled into a button battery.

[0248] The above button cell was subjected to various electrical performance tests on a blue battery tester, the test condition was 25°C, and the charging voltage limit was 0.005-2V.

[0249] (1) First discharge specific capacity and first coulombic efficiency

[0250] The charge and discharge were carried out at a rate of 0.1C, and the first discharge specific capacity and the first coulombic efficiency were tested. The test results are shown in Table 2.

[0251] (2) Cycle performance

[0252] The charge and discharge cycles were performed 200 times at a rate of 0.1C, and the 200th discharge specific capacity was recorded as the 200-cycle retention capacity. The test results are shown in Table 2.

[0253] The capacity retention rate after 200 cycles at 0.1C rate = first discharge specific capacity / 200 cycle retention capacity*100%.

[0254] Table 2

[0255]

[0256] (3) Rate performance

[0257] The test conditions for rate performance are: rate charge and discharge at a current density of 0.1 mA / g-3 mA / g, and the charging voltage is limited to 0.005-2 V. The rate performance test was carried out at different current densities (0.1 mA / g, 0.2 mA / g, 0.5 mA / g, 1 mA / g, 2 mA / g, 3 mA / g), and the rate capacity retention results of Example 1 and Comparative Examples 1-3 are shown in Table 3.

[0258] Table 3

[0259]

[0260] As shown in Table 1-3, compared with Comparative Examples 1-3, the first discharge specific capacity of the silicon-carbon composite material obtained in Example 1-17 is above 2250 mAh / g, the first efficiency is above 95%, and the rate capacity retention rate can still reach 81.2% at a high current density of 3 mA / g, with excellent cycle and rate performance. This is due to the multiple guarantees of the porous core + cluster structure + hollow carbon layer, which significantly improves the volume expansion defect of the silicon material, further increases the diffusion of lithium ions, and significantly improves the rate performance, first efficiency and cycle stability of the silicon-carbon composite material.

[0261] Compared with Examples 1-17, the charge transfer internal resistance of Comparative Example 2 is larger and the cycle performance is very poor. This is because there is no gap between the first carbon layer and the second carbon layer of Comparative Example 2, which cannot alleviate the volume expansion of the silicon material, and exhibits the original performance of silicon (i.e., high internal resistance, high expansion defects), and cannot form a pore structure, which is not conducive to electron transmission.

[0262] Compared with Examples 1-16, the charge transfer internal resistance of Comparative Example 3 is larger and the electrochemical performance is poor. This is because Comparative Example 3 lacks a cluster structure, and there are pores between the particles that make up the cluster structure, which can double the volume expansion of silicon and tin. Compared with Example 17, the first efficiency and cycle stability of the two are comparable, but the silicon content of Comparative Example 3 is much lower than that of Example 17, and its first discharge specific capacity is much lower than that of Example 17.

Claims

1. A silicon-carbon composite material, characterized in that: It includes a cluster structure and a third carbon layer covering the cluster structure; Among them, the cluster structure includes a plurality of silicon-carbon composite particles, pores are distributed between the plurality of silicon-carbon composite particles, the silicon-carbon composite particles have a core-shell structure, which includes an inner core and an outer shell covering the inner core, the outer shell includes a first carbon layer and a second carbon layer in sequence along a direction away from the inner core, the first carbon layer contains a conductive carbon material with a three-dimensional structure, there is an annular gap between the second carbon layer and the first carbon layer, and the inner core includes porous silicon nanoparticles.

2. The silicon-carbon composite material according to claim 1, characterized in that: The silicon-carbon composite material meets one or more of the following conditions: a. The porous silicon nanoparticles are doped with heteroatoms; the heteroatoms are preferably one or more of phosphorus, boron, nitrogen and sulfur; b. The third carbon layer is further coated with a fourth carbon layer, wherein the fourth carbon layer is a chestnut-shaped carbon layer; the chestnut-shaped carbon layer is preferably further coated with a graphene layer; c. The particle size of the silicon-carbon composite particles is 300-420nm; d. The conductive carbon material having a three-dimensional structure is a carbon nanotube, which is preferably a single-walled carbon nanotube and / or a multi-walled carbon nanotube, more preferably a multi-walled carbon nanotube; the inner wall diameter of the carbon nanotube is preferably 1-5 nm, such as 2-4 nm.

3. A method for preparing a silicon-carbon composite material, characterized in that: It includes the following steps: S1. Performing a first carbon coating on porous silicon nanoparticles to obtain a first precursor; wherein the coating material of the first carbon coating includes a conductive carbon material having a three-dimensional structure; S2, coating the first precursor with silicon dioxide to form a silicon dioxide layer to obtain a second precursor; S3, mixing the aqueous dispersion of the second precursor and the oil phase solution containing an emulsifier, removing the solvent and performing heat treatment to obtain a third precursor; S4, performing a second carbon coating on the third precursor and removing the silicon dioxide layer to obtain.

4. The method for preparing the silicon-carbon composite material according to claim 3, characterized in that: Step S1 uses a solvent gel method to perform a first carbon coating on porous silicon nanoparticles, comprising the following steps: S1-1, ultrasonically dispersing the surfactant and carbon nanotubes in water to form spherical micelles; Preferably, in step S1-1, the molar mass ratio of the surfactant to the carbon nanotube is (0.3-0.65) mol: (0.1-0.5) g, for example, 0.4 mol: 0.2 g; Preferably, the carbon nanotubes in step S1-1 are single-walled carbon nanotubes and / or multi-walled carbon nanotubes, preferably multi-walled carbon nanotubes; Preferably, the inner wall diameter of the carbon nanotube in step S1-1 is 1-5 nm, for example 2-4 nm; Preferably, the surfactant in step S1-1 is one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride, dodecyldimethylbenzylammonium bromide and hexadecyldimethylbenzylammonium bromide; S1-2, adding the coating material monomer, nitrogen source and catalyst, stirring to obtain a sol; Preferably, the nitrogen source in step S1-2 is one or more of p-nitroaniline, melamine, triethylamine, pyridine and azobis(ethylbutyronitrile); Preferably, the catalyst in step S1-2 is an alkali compound, wherein the alkali compound is preferably one or more of sodium carbonate, sodium hydroxide and sodium citrate; Preferably, the coating material monomers in step S1-2 are resorcinol and formaldehyde; more preferably, the molar ratio of resorcinol to formaldehyde is (1-3): (1-3); Preferably, the molar ratio of the coating material monomer, nitrogen source and catalyst in step S1-2 to the surfactant in step S1-1 is (1.0-2.0): (0.01-0.09): (0.007-0.03): (0.3-0.65); S1-3, adding porous silicon to obtain a core-shell colloid; Preferably, the molar ratio of the porous silicon in step S1-3 to the catalyst in step S1-2 is (4.0-6.0): (0.007-0.03); S1-4, heating and polymerization to obtain carbon-encapsulated porous silicon; Preferably, the polymerization temperature in step S1-4 is 80-100°C; Preferably, the polymerization time in step S1-4 is 8-24h; S1-5, carbonization, the gel polymer forms the first carbon layer; Preferably, the carbonization temperature in step S1-5 is 550-850°C; Preferably, the carbonization time in step S1-5 is 8-24 hours; Preferably, step S1-5 further includes rinsing and drying after the carbonization; wherein, preferably, the rinsing uses water and / or ethanol.

5. The method for preparing the silicon-carbon composite material according to claim 3, characterized in that: Step S2 includes the following steps: The first precursor, the silicon source and the ammonia solution are mixed, acid washed and heat treated to obtain a second precursor; Preferably, the silicon source in step S2 is a silicate or a silicate; more preferably, the silicate is ethyl orthosilicate and / or methyl orthosilicate; more preferably, the silicate is one or more of sodium silicate, potassium silicate, magnesium silicate and iron silicate; Preferably, the ammonia solution in step S2 contains 25%-30% ammonia by mass, for example 28%; Preferably, in step S2, the mass volume ratio of the first precursor, the silicon source and the ammonia solution is (1-3) g: (3-10) mL: (240-260) mL; Preferably, the temperature of the heat treatment in step S2 is 550-900°C; Preferably, the heat treatment time in step S2 is 8-15h; Preferably, in step S2, the rate of heating from room temperature to the temperature of the heat treatment is 1-10°C / min; Alternatively, step S3 satisfies one or more of the following conditions af: a. The aqueous dispersion of the second precursor comprises a second precursor, a surfactant and water; wherein the surfactant is one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride, dodecyldimethylbenzylammonium bromide and hexadecyldimethylbenzylammonium bromide, such as hexadecyltrimethylammonium bromide; b. The ratio of the second precursor, the surfactant and the water is (1-3) g: (0.2-0.65) mol: 300 mL, for example 2.5 g: 0.45 mol: 300 mL; c. The emulsifier is an emulsifier having a hydrophile-lipophile balance value of 3-8, preferably an emulsifier having a hydrophile-lipophile balance value (HLB) of 4-7, and more preferably one or more of propylene glycol fatty acid ester, diethylene glycol monooleate, monostearate glyceryl and diethylene glycol monolaurate, such as diethylene glycol monooleate or monostearate glyceryl; d. The oil phase solvent in the oil phase solution containing an emulsifier is an olefin having 12 to 28 carbon atoms, such as 1-octadecene; e. The mass percentage of the emulsifier in the oil phase solution containing the emulsifier is 0.5-1wt%, for example 0.8wt%; f. The method for removing the solvent is evaporation, preferably, the temperature during evaporation is 95-98°C; g. The heat treatment temperature is 450-600 ℃, for example 550 ℃; h. The heat treatment time is 0.5-1.5h, for example 1h.

6. The method for preparing the silicon-carbon composite material according to claim 3, characterized in that: Step S4: the coating material during the second carbon coating includes a conductive carbon material having a three-dimensional structure; Wherein, the conductive carbon material with a three-dimensional structure is preferably carbon nanotubes; further preferably, the carbon nanotubes are single-walled carbon nanotubes and / or multi-walled carbon nanotubes, and most preferably multi-walled carbon nanotubes; more preferably, in step S3, the ratio of the surfactant to the carbon nanotubes in the aqueous dispersion of the second precursor is (0.2-0.65) mmol: ((0.1-0.5) g, for example 0.3 mmol: 0.23 g or 0.5 mmol: 0.23 g; and / or, in step S4, the coating material during the second carbon coating includes heteroatoms; Preferably, the heteroatom is one or more of phosphorus, boron, nitrogen and sulfur, such as nitrogen; more preferably, when the heteroatom is nitrogen, the nitrogen source is one or more of p-nitroaniline, nitroaniline, melamine, triethylamine, pyridine and azobis(ethylbutyronitrile), such as p-nitroaniline; And / or, in step S4, the carbon source in the coating material during the second carbon coating comprises phenolic resin and / or asphalt; Preferably, the carbon source comprises a phenolic resin; more preferably, the method for preparing the third precursor by subjecting it to a second carbon coating comprises the following steps: mixing resorcinol, formaldehyde, a catalyst and the third precursor, performing a polymerization reaction and a carbonization treatment, wherein the above steps satisfy one or more of the following conditions ae: a. The molar ratio of the formaldehyde to the resorcinol is (500-1000): (0.5-1.0), for example 1000:1; b. The catalyst is a base, preferably sodium carbonate, sodium hydroxide or sodium citrate, such as sodium carbonate; c. The molar ratio of the resorcinol to the catalyst is (0.5-1.0):(0.007-0.03), for example 0.5:0.01; d. The carbonization temperature is 600-850°C, for example 650 or 700°C; e. The carbonization time is 8-24h, for example 15h.

7. The method for preparing the silicon-carbon composite material according to claim 3, characterized in that: The step S4 further includes the following steps: S5. The product obtained in step S4 is recorded as a fourth precursor. In step S5, the fourth precursor is coated with a chestnut-shaped carbon layer. Preferably, the fourth precursor is coated with a chestnut-shaped carbon layer by a chemical bath deposition method, which includes the following steps: S5-1, ultrasonically dispersing the fourth precursor in a quaternary ammonium salt aqueous solution to obtain a fourth precursor dispersion; adding an aqueous solution containing a nickel salt and an initiator to the fourth precursor dispersion, stirring, adding ammonia water, reacting under stirring, centrifuging, and drying to obtain a composite material A; Preferably, the quaternary ammonium salt is one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride, dodecyldimethylbenzylammonium bromide and hexadecyldimethylbenzylammonium bromide; Preferably, the mass ratio of the fourth precursor to the quaternary ammonium salt is (0.5-1.0):(0.009-0.05), for example, 0.8:0.01; Preferably, the nickel salt is nickel acetate, nickel nitrate or nickel sulfate, for example, nickel acetate; Preferably, the initiator is one or more of potassium persulfate, sodium persulfate and potassium hydrogen persulfate, for example, potassium persulfate; Preferably, the mass ratio of the nickel salt, the initiator and the fourth precursor is (0.1-0.5):(0.02-0.1):(0.5-1.0), for example, 0.1:0.05:0.8; S5-2, heat-treating the composite material A to obtain a composite material B; Preferably, the heat treatment temperature is 350-600°C, for example 450°C; Preferably, the constant temperature time of the heat treatment is 8-24 hours, for example 10 hours; S5-3, adding the composite material B into a surfactant aqueous solution, and sequentially adding a coating material monomer and an initiator, reacting under stirring, centrifuging, washing, and drying to obtain a composite material C; Preferably, the surfactant is an anionic surfactant, more preferably, the anionic surfactant is one or more of sodium dodecylbenzenesulfonate, hexadecyltrimethylammonium p-toluenesulfonate, sodium dodecylsulfonate and sodium α-olefinsulfonate; Preferably, the initiator is one or more of potassium persulfate, sodium persulfate and potassium hydrogen persulfate; Preferably, the mass volume ratio of the surfactant, the coating material monomer and the initiator is (3-10) mg: (0.1-0.3) ml: (0.25-0.65) g, for example 7 mg: 0.2 ml: 0.38 g; Preferably, the coating material monomer is pyrrole and / or pyridine; S5-4, calcining the composite material C, and cooling to obtain a composite material D; the composite material D comprises a nickel layer and a carbon layer; Preferably, the calcination temperature is 650-850°C, for example 650°C; Preferably, the calcination time is 8-24h, for example 15h; S5-5, treating the composite material D with acid to remove the nickel layer, washing, and drying to form a chestnut-shaped carbon layer; Preferably, the acid used in the acid treatment is one or more of hydrochloric acid, sulfuric acid and nitric acid; Preferably, the concentration of the acid is 1-10 mol / L, such as 5 mol / L.

8. A silicon-carbon composite material, characterized in that: The silicon-carbon composite material is prepared by the preparation method of any one of claims 3 to 7.

9. A pole piece, characterized in that: It comprises the silicon-carbon composite material as described in any one of claims 1-2 and 8.

10. A battery, characterized in that: It comprises the pole piece as claimed in claim 9.

Citation Information

Patent Citations

  • Preparation method and application of multilayer carbon-coated silicon-carbon composite material

    CN118712370A

Cited By

  • Preparation method of vapor deposition silicon carbon material based on supercritical carrier gas

    CN120767282A

  • A method for preparing a silicon-carbon material by vapor deposition based on a supercritical carrier gas

    CN120767282B

  • Preparation method of improved silicon-carbon composite negative electrode material and lithium ion battery

    CN120887407A

  • Preparation method of improved silicon-carbon composite negative electrode material and lithium ion battery

    CN120887407B

  • Core-shell structure silicon-carbon negative electrode material and preparation method and application thereof

    CN121172114A